2023
DOI: 10.1002/agr.21800
|View full text |Cite
|
Sign up to set email alerts
|

The role of agricultural sector performance in attracting foreign direct investment in the food and beverages sector. Evidence from planned investments in Africa

Abstract: Using a novel dataset on foreign direct investment (FDI), this paper analyzes the correlates of planned FDI in the food and beverages sector in 49 African countries over the period 2003–2017. It applies the random effects model and augments the standard specification of FDI determinants with a set of factors related to the agricultural sector performance, hypothesized to be essential from the perspective of supply chain linkages and access to raw materials. The results indicate that well‐performing and well‐ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…The results indicated that it is the second most influential factor on Investment Decision with a strong impact (f 2 = 0.385). To a certain extent, it is consistent with the study of Kubik (2023) stating that the well-performed and well-invested agricultural sector of the host country is the main factor influencing location choice of MNEs in the food and beverage sector.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The results indicated that it is the second most influential factor on Investment Decision with a strong impact (f 2 = 0.385). To a certain extent, it is consistent with the study of Kubik (2023) stating that the well-performed and well-invested agricultural sector of the host country is the main factor influencing location choice of MNEs in the food and beverage sector.…”
Section: Discussionsupporting
confidence: 87%
“…Estimated by fixed effects for the panel data, Farr (2017) found that a new variable which measured energy imports as a share of total energy usage was statistically significant and negative to FDI inflows to the agricultural sector of 21 Latin American developing countries. Kubik (2023) found that the performance of the agricultural sector of the host country has a significant impact on the location choice of MNEs, using data of 49 African countries in the period 2003-2017. The author used agricultural production, value added, private and public investment, and the availability of agricultural land to represent the performance of the agricultural sector.…”
Section: Theoretical Foundationmentioning
confidence: 99%
See 2 more Smart Citations